CRITICAL COMMUNICATION PEDAGOGY AT EDUCATIONAL CENTERS - Roseli de Mello; Rosa Larena (Ediciones Universidad de Salamanca, 2009)
Educational researches and proposals should be founded on successful theories and projects recognized by the international scientific community. Based on this premise, we describe Learning Communities as an educational proposal that involves the implementation of theoretical perspectives with a dialogic and critical approach aimed at quality learning for everyone and at overcoming situations of inequality and exclusion. To this end, this article is structured into two distinct parts. The first discusses several theoretical proposals (while also contemplating interdisciplinarity) from the perspective of critical communication. The second part describes the educational experience of the Escuela de Personas Adultas of La Verneda de Sant Martí, the first Learning Community, as well as the processes to bring about the transformation of educational centers in Learning Communities, a proposal that is being disseminated by different countries based on the standpoint of critical communication pedagogy.